(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The meeting of the Semitic prophet Musa with Kydyr is described in Islamic literature, but was not widely known. Most readers present Kydyr as a mythical figure in Islam. In fact, Kydyr is one of the elements that entered the Islamic society from the Aryan society. That is why his place in Islam is unclear: sometimes he is mentioned as a prophet, sometimes he is described as a spirit that supports the lost, then as a person who became immortal by drinking mudi water. This proverb says that Kydyr is a person from a different society and that his knowledge is far superior to that of the Semitic prophets.